The Experimental Evaluation of Cutting Ability with Modified by ECoDM Strips Work Surface - M.G. Kiselev (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2014)
Article is devoted to the experimental evaluation of cutting ability with modified by ECoDM strips work surface. The article shown that making the cutting ability of surface provided by forming thereon during ECoDM recesses (holes) with the edges of the solidified metal nodules. Found that the height of the sag determined by the capacitance of the storage capacitor and the voltage on it, which increases with increasing it. Experimentally proved that these structural elements are capable of shooting chips when cutting materials whose hardness is lower than the hardness of the steel strips. The experimental results, reflecting the influence of height on working surface sagging strips on the intensity of cutting its range of materials. Proceeding from the peculiarities of the process of sawing materials such tool, developed recommendations for the practical use of the research results.